Identification and in silico characterization of a novel p.P208PfsX1 mutation in V-ATPase a3 subunit associated with autosomal recessive osteopetrosis in a Pakistani family - Ajmal, Muhammad (2018)
Background: Osteopetrosis is a rare inherited bone disorder mainly described as an increased bone density caused by defective osteoclastic bone resorption. To date, genetic variants of eleven genes have been reported so far to be associated with different types of osteopetrosis. However, malignant infantile osteopetrosis, a lethal form of the disease, is mostly (50%) caused by mutation(s) in TCIRG1 gene. In this study, we investigated a consanguineous Pakistani family clinically and genetically to elucidate underlying molecular basis of the infantile osteopetrosis. Methods: DNA samples from five family members were subjected to SNP-array based whole genome homozygosity mapping. Data was analyzed and potentially pathogenic mutation was identified by Sanger sequencing of two affected as well as three phenotypically healthy individuals in the family. The significance of identified pathogenic variation and its impact on protein structure and function was studied using various bioinformatics tools. Results: DNA samples from five family members were subjected to genome-wide SNP array genotyping and homozygosity mapping which identified ~4 Mb region on chr11 harboring the TCIRG1 gene. Sanger sequencing unveiled a novel homozygous deletion c. 624delC in exon 6 of the TCIRG1 gene encodes a3 subunit of V-ATPase complex. The identified deletion resulted in a frame shift producing a truncated protein of 208 aa. In silico analysis of premature termination of the a3 subunit of V-ATPase complex revealed deleterious effects on the protein structure, predicting impaired or complete loss of V-ATPase function causing infantile osteopetrosis. Conclusions: Since a3 subunit of V-ATPase complex plays a crucial role in bone resorption process, structurally abnormal a3 subunit might have adversely affected bone resorption process, leading to infantile osteopetrosis in Pakistani family. Therefore, the present study not only expands the genotypic spectrum of osteopetrosis but also improve understandings of the role of V-ATPase a3 subunit in bone resorption process. Moreover, our findings should help in genetic counseling and provide further insight into the disease pathogenesis and potential targeted therapy.